Large language models overcome the challenges of unstructured text data in ecology - Castro, Andry (2024)
Funding Information: AC was supported by a grant ( PRT/BD/152100/2021 ) financed by the Portuguese Foundation for Science and Technology (FCT) under MIT Portugal Program. AC and CC acknowledge support from FCT through support to CEG/IGOT Research Unit ( UIDB/00295/2020 and UIDP/00295/2020 ). JP was funded through FCT for funds to GHTM ( UID/04413/2020 ). LR was funded through the FCT contract \u2018 CEECIND/00445/2017 \u2019 under the \u2018Stimulus of Scientific Employment\u2014Individual Support\u2019 and by FCT \u2018UNRAVEL\u2019 project ( PTDC/BIA-ECO/0207/2020 ; https://doi.org/10.54499/PTDC/BIA-ECO/0207/2020 ). PP acknowledge support from the Czech Science Foundation (project no. 23-07278S ). Publisher Copyright: © 2024 The Authors